إصلاح جامعة الدول العربية - عوينات، نجيب بن عمر Owainat, Najib Bin Omar (صلاح الدين دكداك, 2013)
إن جامعة الدول العربية تتعرض للكثير من النقد سواء من حيث أداؤها أو من حيث آلياتها أو درجة الإلتزام بما تصدره من قرارات، ولا شك في أن هناك جوانب قصور أساسية في الجامعة لعل من أهمها ميثاقها الحالي وعدم قدرتها على تسوية النزاعات العربية، بالإضافة إلى عديد من المشاكل الإضافية مثل الخلافات المتصاعدة وغياب المصداقية وعدم القدرة على الاتفاق. \ إن الأزمة التي تواجه جامعة الدول العربية هي بالتأكيد أزمة أداء.. لا أزمة وجود لأن أسباب وجودها لا تزال قائمة والاحتياج العربي إلى دورها لا يزال باقيا، وهنا على الدول العربية أن ترتب أوضاعها بحال يختلف عما كان عليه وليس ثمة شك في أن تطوير جامعة الدول العربية وإصلاحها بات أمرا لازما لا غنى عنه إن أريد لها أن تواصل بقائها وتدافع عن مصالح أعضائها. وفي هذا السياق، تقدمت عدة دول عربية بعدد من المبادرات والمقترحات تحت شعار تفعيل الجامعة وتطوير الأمانة العامة وتعديل الميثاق خصوصا بعد أحداث 11 سبتمبر 2001 حين تتكاثر التحديات الخارجية وتتزايد المتغيرات الدولية في ضوء إعلان الولايات المتحدة الأمريكية عزمها تغيير الخارطة السياسية للمنطقة العربية وفق المعايير والمصالح الأمريكية تحت مظلة محاربة الإرهاب وإحترام حقوق الإنسان. لذلك فإن الحديث عن إصلاح جامعة الدول العربية والمبادرات المطروحة في هذه المرحلة لا يمكن فصلها عن هذه التطورات الإقليمية والعالمية وتداعياتها. Been subject to a great deal of criticism, both regarding its performance and mechanisms as well as the degree of compliance with its resolutions. Undoubtedly, there are essential shortcomings with the league, most notably its current charter and its inability to settle inter- Arab disputes, in addition to many of its extra problems such as escalating disagreements, lack of credibility, and failure of reaching a consensus. \ As a matter of fact, the crisis facing the Arab League is certainly one of performance and not of legitimacy, because its raison d’être is still valid and the Arabs’ need for its role is still vivid. Therefore, Arab states have to settle their internal situations in a way that is different from the past, as there is little doubt that reforming the Arab League has become so indispensable that it cannot do without it if its survival to continue to defend the interests of its members is still of interest for them. \ In this context, several Arab countries have made a number of initiatives and proposals seeking to reform the league, improve the Secretariat, and amend its Charter, especially after the events of 11 September 2001. Since then, external challenges and growing international realignments in light of America’s expressed vow to change the political map of the Arab world according to the perception and interests of the United States under the pretext of fighting terrorism and observing human rights. Therefore, the talk about reforming the Arab League and the proposed initiatives at this stage cannot be separated from these regional and global developments and their implications.
Keywords: النزاعات العربية -- الجامعة العربية -- العالم العربي -- النظم السياسية -- العلاقات الدولية -- إصلاح جامعة الدول العربية -- القضية الفلسطينية